EDUKASI GAYA HIDUP HALAL DI KALANGAN KOMUNITAS GENERASI MILENIAL - Muhammad Nusran; Puadi Haming; Etik Prihatin; Sitti Musdalifah Hasrin; Nurlaila Abdullah (International Journal Mathla’ul Anwar of Halal Issues, 2021)
The concept of halal is an important factor that must be considered in the halal lifestyle of Muslim consumers, not only in consuming food, but as a factor of food safety, cleanliness and assurance of quality, quality and nutrition of what is consumed. According to Nusran and Mohd Azemi (2021), Halal is a value system and lifestyle adopted by Muslims. Halal means permissible in Islam – prepared according to certain parameters of Islamic Law. (Fuad Mohd, 2019). Halal lifestyle education is needed as one of the handling of various serious problems that arise due to the low awareness and understanding of young millennial consumers about the halal concept by increasing the empowerment of the millennial generation about the halal lifestyle. This paper is intended to determine the effect of awareness and knowledge of the halal concept on the millennial generation. Descriptive statistics are used to identify respondents' attitudes towards halal food requirements. The method of collecting data in the field uses a questionnaire system and purposive method which is processed by linear regression analysis method. The results of the analysis obtained are that there is a significant relationship between halal certification, halal lifestyle, awareness and knowledge of halal concepts in the millennial generation. Halal lifestyle education affects awareness and knowledge about halal lifestyle. The official halal certificate has a significant effect on the buying interest of millennial consumers. Awareness and understanding of the concept of halal have a low effect on the buying interest of the millennial generation. From the existing data, it can be concluded that the educational activities carried out can increase the knowledge of the millennial generation about the halal lifestyle and understanding of the point of prohibition of food.